In situ Linkage of Fungal and Bacterial Proliferation to Microbiologically Influenced Corrosion in B20 Biodiesel Storage Tanks - Stamps, Blake W.; Bojanowski, Caitlin L.; Drake, Carrie A.; Nunn, Heather S.; Lloyd, Pamela F.; Floyd, James G.; Emmerich, Katelyn A.; Neal, Abby R.; Crookes-Goodson, Wendy J.; Stevenson, Bradley S. (Frontiers in Microbiology, 2020)
Biodiesel is a renewable substitute, or extender, for petroleum diesel that is composed of a mixture of fatty acid methyl esters (FAME) derived from plant or animal fats. Ultra-low sulfur diesel (ULSD) blended with up to 20% FAME can be used interchangeably with ULSD, is compatible with existing infrastructure, but is also more susceptible to biodegradation. Microbial proliferation and fuel degradation in biodiesel blends has been linked to microbiologically influenced corrosion (MIC), but this has not been studied previously in situ. We, therefore, conducted a yearlong study of B20 storage tanks in operation at two locations, identified the microorganisms associated with visible fuel fouling, and measured in situ corrosion. The bacterial populations were more diverse than the fungal populations, and largely unique to each location. The bacterial populations included members of the Acetobacteraceae, Clostridiaceae, and Proteobacteria. The abundant Eukaryotes at both locations consisted of the same taxa, including a filamentous fungus within the family Trichocomaceae, not yet widely recognized as a contaminant of petroleum fuels, and the Saccharomycetaceae family of yeasts. Increases in the absolute and relative abundances of the Trichocomaceae were correlated with significant, visible fouling and pitting corrosion. This study identified the relationship between fouling of B20 with increased rates of corrosion and the microorganisms responsible, largely at the bottom of the sampled storage tanks.